Data Mining Techniques in Monitoring Customers’ Sector - Jelonek, D. (Электронное моделирование, 2007)
Получение информации о секторе клиентов является для предприятия важным фактором повышения конкурентоспособности. Эффективными средствами при обработке и использовании информации в процессе принятия решений являются методики получения данных. Описаны широкие возможности технологии Data Mining Techniques на основе информационных ресурсов системы Client relation management. Отримання інформації про сектор клієнтів для підприємства є важливим фактором під вищення конкурентоспроможності. Ефективними засобами при обробці і використанні інформації у процесі прийняття рішень є методики отримання даних. Описано широкі можливості технології Data Mining Techniques на основі інформаційних ресурсів системи Client relation management. An area where enterprises are increasingly looking for the opportunity to gain competitive prevalence is that of acquiring knowledge about enterprise’s environment, particularly on the customer’s sector. An effective tool in processing and using the knowledge in decision processes is Data Mining Techniques. Wide possibilities of Data Mining Technique based on information resources of Client relation management system are described.